Factors influencing caries incidence in permanent teeth in children/adolescents under and after anti-neoplastic treatment - Ewa Krasuska-Sławińska; Agnieszka Brożyna; Bożenna Dembowska-Bagińska; Dorota Olczak-Kowalczyk (Contemporary Oncology)
Aim of the study : To determine reasons for the increase in caries among children/adolescents treated for neoplasms. Material and methods : Health promoting behaviour, oral hygiene (PLI), gingiva (GI), dentition (DMFt/DMFs, number of teeth with white spot lesions (WSL), and enamel defects (ED) were assessed in three groups of 60 patients each. The three groups were as follows: under chemotherapy (CH), after chemotherapy (PCH), and generally healthy (CG). Medical files supplied information on neoplasm type, chemotherapeutic type and dose, age at treatment start, chemotherapy duration, and complications. Statistical analysis was performed with Mann-Whitney U test and Spearman’s rho test. Results: The age at which chemotherapy was started/its duration was 5.9 ±4.0/1.3 ±0.5 years in PCH and 9.12 ±4.44/0.8 ±0.3 years in CH; PCH completed treatment 4.9 ±3.4 years ago. Chemotherapy most often included vincristine (VCR), etoposide (VP-16), adriamycin (ADM), cyclophosphamide (CTX), cisplatin (CDDP), and ifosphamide (IF). Mucositis occurrence was 28.33% in PCH and 45.00% in CH; vomiting occurrence was 43.33% and 50.00%, respectively. Nutrition and prophylaxis mistakes occurred more often in CH/PCH than in CG; PLI, GI, caries incidence and severity, and the number of teeth with WSL were higher. Correlation between caries incidence and chemotherapeutic type and dose, age at treatment start and treatment duration, mucositis, emesis, PLI, GI, ED, no fluoride prophylaxis, and nutritional mistakes was established. Ifosphamide and mucositis treatment played a major role in chemotherapy; after chemotherapy – ED and CTX, ADM, IF, and VP-16. Conclusions : Caries in permanent teeth in children/adolescents undergoing chemotherapy result from nutritional mistakes, poor prophylaxis, and indirectly from chemotherapy complications (first mucositis and emesis, and later developmental ED).